tomato Morphological characterization and molecular validation for ToLCV resistance (Ty-2 and Ty-3 genes) in tomato (Solanum lycopersicum) - DHITAL, SUSHIMA; YADAV, R K; LATA, SUMAN; HUSSAIN, ZAKIR; CHOUDHARY, H; SOLANKE, AMOLKUMAR U; D, VINAY N (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during the rainy (kharif) season of 2019 and 2020 at ICAR-Indian Agricultural Research Institute, New Delhi to identify the potential genotypes having good horticultural traits along with strong and durable resistance against ToLCV disease of tomato (Solanum lycopersicum L.). A diverse set of 30 tomato genotypes carrying different Ty genes were screened out at phenotypic and genotypic level. First appearance/symptom of tomato leaf curl virus (ToLCV) disease was recorded in Pusa 120 only after 16 days of transplanting (DAT). Within 30 days of transplanting most of the genotypes, viz. Pusa 120, DT12, DT16, DT6 and Pusa Sheetal recorded 80 to 100 PDI (per cent disease incidence) and they were rated as highly susceptible to ToLCV. While at 90 DAT ToLCVincidence (≤15%) was observed in DT2, DT8, DT17, DT20 and DT30 and were categorized a resistant. None of the genotype was found as highly resistant. Four genotypes, viz. DT2, DT10, DT20 and DT30 showed presence of both resistant genes Ty-2 and Ty-3 at genotypic level. These promising genotypes will be useful as parental material to develop lines/hybrids carrying multiple genes against both monopartite and bipartite viruses for strong and durable resistance against ToLCV disease.